2016
DOI: 10.17269/cjph.107.5399
|View full text |Cite
|
Sign up to set email alerts
|

Restaurant inspection frequency: The RestoFreq Study

Abstract: OBJECTIVES: Foodborne illness is an important contributor to morbidity and health system costs in Canada. Using number of critical hazards as a proxy for food safety, we sought to better understand how to improve food safety in restaurants. We compared the current standard of annual inspections to twice-yearly inspections among restaurants "at risk" for food safety infractions. These were restaurants that had three or more elevated-risk inspection ratings in the preceding 36 months. METHODS:We conducted a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
1
6
1
Order By: Relevance
“…Two studies found no significant difference in the number of violations and increased inspection frequency. This was noted to be consistent with literature in that increased inspection frequency was not associated with decreased violations (Newbold et al, n.d.;Medu et al, 2016). Further, the study by Newbold et al, also…”
Section: Impacts Of Restaurant Inspection Frequencysupporting
confidence: 90%
See 3 more Smart Citations
“…Two studies found no significant difference in the number of violations and increased inspection frequency. This was noted to be consistent with literature in that increased inspection frequency was not associated with decreased violations (Newbold et al, n.d.;Medu et al, 2016). Further, the study by Newbold et al, also…”
Section: Impacts Of Restaurant Inspection Frequencysupporting
confidence: 90%
“…For this literature review, a combination of peerreviewed journal articles and publications were used, as well as grey literature from various sources such as BCIT Environmental Health Journal (Besharah, 2015;Thandi, 2020;Tung, 2018). Of the four articles chosen for this literature review, two explore restaurant inspection frequency and effects on food safety compliance and number of critical hazards per inspection (Newbold et al, n.d.;Medu et al, 2016).…”
Section: Impacts Of Restaurant Inspection Frequencymentioning
confidence: 99%
See 2 more Smart Citations
“…Leinwand et al 8 found that an increase in inspection frequency decreased violations in nonchain restaurants, but not in chain restaurants. On the other hand, some studies have not found an association between inspection frequency and inspection results 9 , 10 . All of these studies have focused on restaurant inspections.…”
Section: Introductionmentioning
confidence: 98%